1, 4-Bis(2′-pyridylethynyl)benzene as a ligand in heteronuclear gold–thallium complexes. Influence of the ancillary ligands on their optical properties12. Issue 15 (21st April 2015) - Arca, Massimiliano; Donamaría, Rocío; Gimeno, M. Concepción; Lippolis, Vito; López-de-Luzuriaga, José M.; Manso, Elena; Monge, Miguel; Olmos, M. Elena
<x xml:space="preserve">Abstract</x> Complexes [Au(C6Cl5)2Tl(L)]n (luminescent) and [Au(C6F5)22Tl2(L)2]n (non-luminescent) (L = 1, 4-bis(2′-pyridylethynyl)benzene) have been synthesized and their crystal structures and photophysical properties have been studied.